THE IMPACT OF TRANSFORMATIONAL LEADERSHIP AND WORKPLACE BULLYING ON SERVICE QUALITY (World Economics and Finance Bulletin, 2025)
To identify the impact of transformational leadership and workplace bullying on service quality in Iraqi universities.